Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.4028/www.scientific.net/kem.254-256.1111
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Apatite Formation on Chemically Modified Cellulose Templates

Abstract: Biomimetic precipitation of calcium phosphate phases (Ca-P) from simulated body fluid (1.5 SBF) on the biopolymer cellulose was studied. The basic crystallization behavior was investigated using highly oriented Langmuir-Blodgett films of cellulose activated in Ca(OH) 2 solution. Using transmission electron microscopy it was shown that the activated cellulose triggered the formation of nano-cyrstalline Ca-P phases, whereas spherical nano-aggregates were found on pure cellulose films. The formation of two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…By changing the ionic character of copolymer micelles in solution, we can vary the formation and composition of the inorganic phase on copolymer micelles in aqueous solutions. Appropriate copolymer design and synthesis and the use of gel-forming self-assembling copolymers, makes possible the formation of macro-sized ordered networks of spherical nanocomposites for a bottom-up approach to materials design, while most previous work has focused on mineralizing the surface of bulk polymers [4][5][6] or forming sub-micron aggregates of organic-inorganic nanocomposites. 7,15 The nanocomposites formed were characterized by electron microscopy, X-ray scattering, and advanced solid-state NMR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By changing the ionic character of copolymer micelles in solution, we can vary the formation and composition of the inorganic phase on copolymer micelles in aqueous solutions. Appropriate copolymer design and synthesis and the use of gel-forming self-assembling copolymers, makes possible the formation of macro-sized ordered networks of spherical nanocomposites for a bottom-up approach to materials design, while most previous work has focused on mineralizing the surface of bulk polymers [4][5][6] or forming sub-micron aggregates of organic-inorganic nanocomposites. 7,15 The nanocomposites formed were characterized by electron microscopy, X-ray scattering, and advanced solid-state NMR.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation of calcium phosphate into the copolymer gel matrix was achieved using aqueous solutions of ammonium dihydrogen phosphate (NH 4 In order to analyze the growth of the ceramic coatings on the micelles, a less-concentrated 0.5 wt% polymer solution (below the critical gel concentration) was also tested. To prepare this sample, 10 mL of the pH 3.0 calcium phosphate solution was mixed with an equal amount of 1.0 wt% pentablock copolymer solution yielding a solution of 0.5 wt% pentablock copolymer, and half of the saturated calcium phosphate ion concentration.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the formation of a bonelike HCA surface layer and the resultant bonebonding ability of an implant can be evaluated by testing the material in an acellular simulated body fluid (SBF) with ion concentrations nearly equal to those of the inorganic part of human blood plasma [3,4]. Since SBF is supersaturated with respect to HCA at 37°C, the solution has been widely used for precipitation of nano-scale calcium phosphate powders and for biomimetic coating of implant surfaces under mild conditions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%